Evaluating healthcare practitioners' views on store-and-forward teledermoscopy services for the diagnosis of skin cancer. (February 2019) - Janda, Monika; Horsham, Caitlin; Koh, Uyen; Gillespie, Nicole; Vagenas, Dimitrios; Loescher, Lois J; Curiel-Lewandrowski, Clara; Hofmann-Wellenhof, Rainer; Peter Soyer, H.
Objective: The aim of the study is to evaluate healthcare practitioners' views on and satisfaction with (i) digital image acquisition and storage and (ii) store-and-forward teledermoscopy services for the diagnosis of skin cancer in their clinical practice. Methods: An online survey was conducted among 59 healthcare practitioners (GPs ( n =17), dermatologists ( n =22), dermatology registrars ( n =18), a dermatology research fellow ( n =1) and a plastic surgeon ( n =1)) to assess usability of digital image acquisition and storage for when the imaging process is conducted by the healthcare practitioners themselves, or by their patients. The study identifies the enablers and barriers of this emerging mode of medical practice. A thematic analysis was used to extract key themes from open-ended responses, which involved identifying themes and patterns within and across participants. Results: Thirty-four healthcare practitioners (58%) had previously used a mobile dermatoscope within their practice. Participants most appreciated its use in their practice for lesion monitoring (59%) and record keeping (39%). Challenges reported were the increased time to support the additional workload (45%), technical issues (33%) and cost of equipment (27%). Practitioners were unsure (36%) or did not advocate teledermoscopy for direct-to-consumer use (41%). Only 23% supported the use of direct-to-consumer teledermoscopy. Conclusion: While most practitioners are receptive to mobile teledermoscopy, there was less support for patient-initiated use, whereby the patient controls the imaging process. As technology improves rapidly it is important to evaluate practitioners' acceptance and satisfaction of evolving telehealth services, moving forward with models of practice where healthcare practitioners and other healthcare providers will feel comfortable engaging in telehealth services.